Editorial Fallow Time and Managing Aerosol Generation in Dental Clinics–Current Evidence and Financial Investment Implications - Fazal Ghani, Fazal Ghani (Journal of Rawalpindi Medical College, 2020)
Recently, the Scottish Dental Clinical Effectiveness Programme (SDCEP) was tasked to perform a rapid review on the guidelines related to factors mitigating the effect of aerosol generation during dental procedures and reduction in fallow-time. Review1, reflecting the tireless work by the SDCEP review board can be truly considered as a report that the profession has been looking for. The SDCEP’s review comes at a time when the science has not been comprehensive and doesn’t outline how to best ensure public and staff safety in the dental clinic.2 He hopes that the government policy and any new instructions will now reflect the recommendations made in this review. Considering the issues of continued frustration of the dental profession, towards the end of June, the Office of the Chief Dental Officers (CDOs) in the UK tasked the SDCEP to get to grips with the matter. It is worth-noting that SDECP3 has been held in high regard for its outstanding work on antimicrobial resistance, antibiotic prophylaxis, dental amalgam, and periodontal care, and has been praised by all the CDOs in the UK four countries including England, Scotland, Wales, and Northern Ireland. In response, the SDCEP immediately convened a multidisciplinary working group to identify and appraise all the available evidence concerning the generation and mitigation of aerosol dentistry and the associated risk of COVID-19 transmission. The aim was to reach a number of agreed position statements informing policy and clinical guidance. The review members’ dedication, commitment, and clinical and academic expertise have been hugely impressive.2 All worked for almost three months and there were; remarkable academics, virologists, physicists, public health officials, and other wet-fingered dentists. The process required hours of virtual meetings piled on top of intensive review work. To complete the review, everyone almost felt like being a student again waking up to spend hours on physics of relevance to aerosol and epidemiology of airborne viral diseases.